Target enrichment of long open reading frames and ultraconserved elements to link microevolution and macroevolution in non‐model organisms. (27th November 2022) - Ortiz‐Sepulveda, Claudia M.; Genete, Mathieu; Blassiau, Christelle; Godé, Cécile; Albrecht, Christian; Vekemans, Xavier; Van Bocxlaer, Bert
Abstract: Despite the increasing accessibility of high‐throughput sequencing, obtaining high‐quality genomic data on non‐model organisms without proximate well‐assembled and annotated genomes remains challenging. Here, we describe a workflow that takes advantage of distant genomic resources and ingroup transcriptomes to select and jointly enrich long open reading frames (ORFs) and ultraconserved elements (UCEs) from genomic samples for integrative studies of microevolutionary and macroevolutionary dynamics. This workflow is applied to samples of the African unionid bivalve tribe Coelaturini (Parreysiinae) at basin and continent‐wide scales. Our results indicate that ORFs are efficiently captured without prior identification of intron‐exon boundaries. The enrichment of UCEs was less successful, but nevertheless produced substantial data sets. Exploratory continent‐wide phylogenetic analyses with ORF supercontigs (>515, 000 parsimony informative sites) resulted in a fully resolved phylogeny, the backbone of which was also retrieved with UCEs (>11, 000 informative sites). Variant calling on ORFs and UCEs of Coelaturini from the Malawi Basin produced 2000 SNPs per population pair. Estimates of nucleotide diversity and population differentiation were similar for ORFs and UCEs. They were low compared to previous estimates in molluscs, but comparable to those in recently diversifying Malawi cichlids and other taxa at an early stage of speciation. Skimming off‐target sequence data from the same enriched libraries of Coelaturini from the Malawi Basin, we reconstructed the maternally‐inherited mitogenome, which displays the gene order inferred for the most recent common ancestor of Unionidae. Overall, our workflow and results provide exciting perspectives for integrative genomic studies of microevolutionary and macroevolutionary dynamics in non‐model organisms.